Copied from Word the same as in first post.

Any explanations or suggestions?

(s112+s222+s332)2 = s114+s224+s334 + 2(s112s222+ s112s332+ s222s332)

(s11+s22+s33)2 = s112+s222+s332 + 2(s11s22+ s11s33+ s22s33) = 0 because sii=0. So

s112+s222+s332 = -2(s11s22+ s11s33+ s22s33)

(s112+s222+s332)2 = 4[s112s222+s112s332+s222s332 + 2(s11+s22+s33)(s11s22s33) and sii=0. So

s112s222+s112s332+s222s332 = ¼(s112+s222+s332)2 and substitute this into first eq to get:

s114+s224+s334 = ½(s112+s222+s332)2 , or in indicial notation:

sii4 = sii2sjj2